Transition to Online Teaching Under COVID-19: The Case Study of UAE University - Aizhan Shomotova (15445346) (2023)
This chapter discusses the role of universities and government in supporting the transition to online teaching, describes the challenges and reflections of academic staff on this transition to online teaching, their research efficiency during the lockdown, and their satisfaction and comfortability with the online teaching experience in general and in the future. This empirical study uses a cross-sectional online survey of faculty members’ experience transitioning to online teaching at UAE University (N = 175 of faculty members). The chapter suggests that the UAEU case study could be treated as a successful example of the urgent transition to online learning and teaching since the vast majority of the faculty members were satisfied with their online teaching experience. Furthermore, results even speak for improved research efficiency, irrespective of gender. Other Information Published in: Social Change and Transformation in the Gulf Region License: https://creativecommons.org/licenses/by/4.0 See chapter on publisher's website: https://dx.doi.org/10.1007/978-981-19-7796-1_9